Intervensi Rolling Massage Dalam Meningkatkan Produksi Asi Pada Ibu Post Partum Di Wilayah Kecamatan Tabungnanen - Jamilah, Sri; Ariani, Sri Purwanti; Indria, Rekha (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Postpartum marks the initiation of lactation, and ideally, newborns should be able to breastfeed from their mothers. Postpartum encompasses the period from 2 hours after the delivery of the placenta up to six weeks thereafter. During this duration, mothers undergo numerous changes, both physically and mentally. A common issue that arises during the postpartum period is the irregularity of breast milk supply. The objective of this community service initiative is to provide Back Massage Rolling to postpartum mothers. The method employed involves demonstrating the rolling massage technique to mothers with infants, aiming to facilitate smoother milk production, especially in the rural communities on the outskirts of the Tabunganen sub-district. The approach includes hands-on demonstrations for mothers with infants, teaching them the rolling massage technique to enhance daily breastfeeding experiences. The conclusion drawn is that a significant portion of the community, particularly mothers with infants, can accurately and effectively demonstrate the application of rolling massage in their daily routines.